Disability, Nazi euthanasia, and the legacy of the Nuremberg medical trial - Burdett, Emmeline (Disability in society, 2024)
"Meticulously shows how the legacy of the Nuremberg Medical Trial has influenced-and continues to influence-debates about euthanasia and disability-related ethical issues across decades"--